The use of the passive voice in the writing of Arab ESL learners / Aws Nabeel Hameed - Aws Nabeel, Hameed (2017)
This study aims to know the understanding of the students regarding the use of English passive voice. There were three main theories used in this study. They are Quirk’s Theory, Corder’s Theory, and Culicover’s Theory. Theory of Quirk’s was used to know and understand the structure of English passive voice. While, theory of Error Analysis was used to analyze the students’ error based on the Linguistic Category Taxonomy particularly for the English passive voice, and Culicover’s Theory was used to find out the syntactical representation using labeled bracketing and the tree diagram. Those three theories were correlated since this study discussed the understanding of the students in using English passive voice. The data was taken from three universities in Malaysia which are; UPM, UKM and UIM, particularly Arab students who are doing their Master and PhD. There were 50 students as the sample in this study. The methods of collecting data were quantitative and qualitative methods. The data analysis in this study was the students’ works, regarding to the forming of English passive voice. The descriptive qualitative method was used in presenting the result of data analysis. There were 6 categories that were included in chapter 4 to show the errors that the students made when using passive voice. The highest percentage of error was 74% in the error category related to the Incorrect Use of Past Participle. While, the lowest percentage of error was 10% for the category of error related to the incorrect use of irregular of have/had.